Global and regional disparities in access to specialist sarcoma services - Tomas Zamora; Eduardo Botello; Thomas Jenkins; Charlotte Jeys; Minna Laitinen; Ajay Puri; Lee Jeys; On behalf of the BOOM consensus meeting participants (Bone & Joint Open)
Aims: Cancer care guidelines have been developed in many subspecialities, usually in advanced health systems. However, there are notable global disparities in healthcare access, which can impact sarcoma care. Unfortunately, there is a lack of global data on this subject. Our aim was to describe access to sarcoma care based on a comprehensive global survey among orthopaedic oncologists, and assess for global as well as regional differences. Methods: A 25-question survey was emailed to the attendees of the 2024 Birmingham Orthopaedic Oncology Meeting and included questions about the respondents’ training and practice, access to sarcoma centres, and specific items for sarcoma diagnosis and treatment. For data analysis and comparison, countries were grouped geographically and per the World Bank’s income classification. Results: A total of 192 specialists from 47 countries completed the survey (67%). Overall, 40% declared that most patients in their country were treated in a specialized sarcoma centre. Declared access to specific diagnostic technology ranged from 69% (translocation studies) to 86% (various immunohistochemistry). Only 31% stated having access to proton therapy and 82% to all possible reconstruction methods. Compromise of ideal surgical management because of prior treatments and financial constraints was declared to have happened regularly in 40% and 17% of practices, respectively. Regions with better-developed healthcare systems had improved access to all aspects surveyed. Similar results were observed when comparing high-income countries against low- to middle-income countries. Conclusion: Our study highlights substantial global and regional disparities in access to sarcoma services, which could potentially impact clinical outcomes. Further studies are needed to clarify this reality. Cite this article: Bone Jt Open 2025;6(4):425–431.